(3GdeZGfe GdeWGHI aj eYGde WGHI (B( (3GdeOjfI(B)s - (3eMeO Hf jYbhH Hf eMeO Hf EHQGgje Hf YeQ, CHh WGgQ, eLO GdOjf GdTjQGRj GdajQhRBHGOj,J (B817 (3g` s ((3CHh HcQ Hf eMeO Hf eMeO Hf CHj GdMSf eMeO Hf agO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B118s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B257 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1747s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs